2002
DOI: 10.1051/lait:2002011
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic, lipolytic and autolytic activities of enterococci strains isolated from Egyptian dairy products

Abstract: -Enterococci were isolated from Egyptian Domiatti and Mish cheeses made from raw milk. The proteolytic, lipolytic and autolytic activities of the isolated strains were studied to select the most appropriate cultures to be used for the enhancement of the organoleptic properties of cheese. The intracellular peptide hydrolase activities of enterococci strains were determined using various synthetic aminopeptidase and dipeptidyl-aminopeptidase substrates. 4-nitrophenyl and 2-nitrophenyl derivatives of fatty acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
2
6
0
2
Order By: Relevance
“…Considering the studies in the literature, it is possible to say that there are many researches about lipolytic enzyme production ability of enterococci species. Lipolytic activity is frequently detected among enterococci [25][26][27]. In our study, E. faecium-97, E. faecium-299, E. faecium-168 and E. faecium-169 showed medium activity.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Considering the studies in the literature, it is possible to say that there are many researches about lipolytic enzyme production ability of enterococci species. Lipolytic activity is frequently detected among enterococci [25][26][27]. In our study, E. faecium-97, E. faecium-299, E. faecium-168 and E. faecium-169 showed medium activity.…”
Section: Resultssupporting
confidence: 53%
“…In our study, E. faecium-97, E. faecium-299, E. faecium-168 and E. faecium-169 showed medium activity. El-Din et al [27] reported lipolytic Enterococcus strains isolated from some dairy product types using different natural or synthetic substrates, including tributyrin. Simonova et al [1] described lipolytic enterococci isolated from meat products (sausage).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Enterococcus was negatively correlated with protein. Wessels et al (Wessels et al, 1990) and Bassem et al (Bassem et al, 2002) also suggested that Enterococcus produced proteolytic enzymes involved in casein degradation. Overall, LAB played a major role in the fermentation of koumiss.…”
Section: Changes In Metabolic Pathways At Different Fermentation Time Points Based On the Kegg Databasementioning
confidence: 99%
“…The detection of lipolytic activity among enterococci of dairy and meat (sausage) origin is more common and measured in higher values. El-Din et al (2002) also described lipolytic enterococci isolated from dairy products using several natural and synthetic substrates, including tributyrin; enterococcal lipases hydrolysed tributyrin more rapidly than other simple triglycerides. On the other hand, measurements of the lipolytic activity of bacteria isolated from dairy and meat products are common and even requested because of the product quality.…”
Section: Resultsmentioning
confidence: 99%